Four women mentioned in The Holy Qura’n as a model of faith and atheism - Younis, Asmaa Wajeh (Journal of Islamic Sciences, 2022)
Women have been mentioned in the Holy Qur’an in many places, and some of them were singled out by mentioning their stories or their names, but there is no woman whose name is explicitly mentioned in the Qur’an except for Maryam. The Quranic miraculous concise style is limited to mentioning the closest method to defining the desired person and the most specific to his identity, according to the requirements of the status and context. The Holy Qur’an came by citing many examples and models of women. From this standpoint, this study dealt with talking about the proverbs in the Qur’an which have a special rhetoric that can realized only by those who know the secrets of the Arabic language. The wisdom of setting proverbs in the Quran is to ease the understanding, the realization and the access to it; so that no one will have an argument on the Day of Resurrection, as all the rational, cosmic and literary evidence points with one breath to "la ilah illa allah" (there is no god but Allah). This study is based on explaining the concept of the proverb as in language and as an idiom, as well as explaining the sections of the proverb, the proverb is divided into two parts: the explicit proverb and the latent proverb, and this study dealt with the types of proverbs in the Holy Qur’an such as the symbolic, anecdotal, and natural proverbs, and this study also clarified the benefits of proverbs in the Qur’an which one of the most important of them was that proverbs have more effect than abstract words, because they bring the image closer, attract attention, subjects the illusion for the mind, and lift the veil from unaware hearts and compose what is needed and bring it closer, and this study is concluded with the most important four models of women- two examples of the bad people and two examples of the believers through Surat Al-Haram, Allah has set two wonderful and clear examples, of the unbelievers and the people of faith, to show the status of the unbelievers by the represent that they are punished for their disbelief and enmity to the believers by punishing people like them without regard for lineage, marital, kinship, or favoritism, so the wife of Noah and Lot’s wife been punished even though they were in the house of prophet-hood, but they disbelieved in Allah and the Prophet, so the marital bond did not save them from the punishment of Allah, and Allah sat an example for a Muslim woman who marries an unbeliever, her husband’s disbelief does not harm her along with her conversion to Islam, this wonderful example of the believers came to indicate that it is their duty to be in such sincerity, honest determination and strength of certainty as these two believers: Aasiya the wife of Pharaoh and Maryam the daughter of Imran.